Overdenture as a restorative option for hypocalcified-hypoplastic amelogenesis imperfecta: a case report. - Assunção, Wirley Goncalves [UNESP]; Barão, Valentim Adelino Ricardo; Kanno, Cláudia Misue [UNESP]; Saito, Célia Tomiko Matida Hamata [UNESP]; Delben, Juliana Aparecida (My University, 2009)
AIM: The aim of this report is to describe the restorative treatment of an 18-year-old patient diagnosed with autosomal recessive hypocalcified-hypoplastic amelogenesis imperfecta (AI). BACKGROUND: Esthetic and functional rehabilitations in AI cases are challenging and should consider individual aspects, such as age, socioeconomic status, AI type, and intraoral condition. REPORT: AI was diagnosed in an 18-year-old patient. SUMMARY: Considering the short length of crowns and roots, patient life expectancy, minimal invasiveness, amount of treatment time required, and lower costs, oral rehabilitation with overdentures provided an adequate functional and esthetic rehabilitation of the patient. CLINICAL SIGNIFICANCE: This report demonstrated overdentures to be a viable, relatively inexpensive, and non-invasive treatment choice of a patient with AI with concerns about treatment longevity, invasiveness, cost, esthetics, and long-term maintenance.
Keywords: adolescent; amelogenesis imperfecta; case report; consanguinity; denture; female; genetics; human; periodontal disease; recessive gene; tooth occlusion; Adolescent; Amelogenesis Imperfecta; Consanguinity; Denture, Overlay; Female; Genes, Recessive; Humans; Tooth Loss; Vertical Dimension